(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
The endeavor of providing a precise and comprehensive definition of the rhetoric, from antiquity to the present day, remains inside the limits of an ongoing activity and has, consequently, produced numerous disparate interpretations and articulations. This situation is a result of a long-standing and uninterrupted rich tradition of the rhetoric, of its interrelation with other disciplines and of its capability to continually generate new fields of research and specialization. Definitions offered by the authors of the antiquity, may be divided in two categories and reduced to two generalized definitions: 1. Rhetoric is an art of civic discourse and 2. Rhetoric is an art of persuasion by words. Neither the antiquity nor the centuries that followed ever proposed a single and constant definition of the rhetoric. However, the numerous attempts to give a strict and comprehensive description of the rhetoric in the antiquity emphasized several basic components of its identity. These are as follows: the art, the persuasion, the public and the language as a particular linguistic form. Each of these components is the object of research of different disciplines which continue to maintain the rhetoric ’s vitality and capability of innovating other intellectual fields.